N-Substituted pyrazole-3-carboxamides as inhibitors of human 15-lipoxygenase. Issue 15 (1st August 2015) - Pelcman, Benjamin; Sanin, Andrei; Nilsson, Peter; Schaal, Wesley; Olofsson, Kristofer; Krog-Jensen, Christian; Forsell, Pontus; Hallberg, Anders; Larhed, Mats; Boesen, Thomas; Kromann, Hasse; Claesson, Hans-Erik
Graphical abstract